A novel V1a receptor antagonist blocks vasopressin-induced changes in the CNS response to emotional stimuli: an fMRI study - Lee, Royce J.; Coccaro, Emil F.; Cremers, Henk; McCarron, Rosemary; Lu, Shi-fang; Brownstein, MIchael; Simon, Neal G. (Frontiers in Systems Neuroscience, 2013)
Background: We hypothesized that RX246, a vasopressin V1a receptor antagonist, blocks the effect of intranasally administered vasopressin on brain processing of angry Ekman faces. An interaction of intranasal and oral drug was predicted in the amygdala. Methods: Twenty-nine consenting right handed healthy male subjects received a baseline fMRI scan while they viewed angry faces. Subsequently, they were randomized to receive oral SRX246 (120mg PO twice a day) or placebo. After an average of 7 days of treatment (range 5-11 days), they were given an acute dose of intranasal vasopressin (40 I.U) or placebo and underwent a second scan 60 min later. The primary outcome was BOLD activity in the amygdala in response to angry faces. Secondary analyses were focused on ROIs in a brain regions previously linked to vasopressin signaling. Results: In subjects randomized to oral placebo-intranasal vasopressin, there was a significantly diminished amygdala BOLD response from the baseline to post-drug scan compared with oral placebo-intranasal placebo subjects. RM-ANOVA of the BOLD signal changes in the amygdala revealed a significant oral drug x intranasal drug x session interaction (F (1, 25) = 4.353, p